Patient-Controlled Analgesia After Cardiac Surgery With Median Sternotomy: No Advantages of Hydromorphone When Compared to Morphine - Wehrfritz, Andreas; Senger, Anne-Sophie; Just, Patrick; Albart, Maximilian; Münchsmeier, Michael; Ihmsen, Harald; Schüttler, Jürgen; Jeleazcov, Christian (Journal of Cardiothoracic and Vascular Anesthesia, 2022)
Objectives: To compare the efficacy, safety, and side effects of hydromorphone and morphine administered as patient-controlled analgesia (PCA) for postoperative pain therapy after cardiac surgery with median sternotomy. Design: A retrospective analysis of data from 2 prospective, single-blinded, randomized trials. Setting: A single-center intensive care unit at a university hospital. Participants: Forty-one adult patients undergoing cardiac surgery with median sternotomy. Interventions: Postoperative pain therapy at the intensive care unit was performed by PCA with intravenously administered bolus doses of 0.2 mg of hydromorphone (n = 21) or 2 mg of morphine (n = 20). Measurements and Main Results: Pain at rest and under deep inspiration regularly was assessed using the 11-point numerical rating scale (NRS). Blood pressure, heart rate, cardiac output, oxygen saturation, and respiratory rate were monitored, and adverse events were registered. The median (range) NRS rating at rest was 1.5 (0-5) after hydromorphone and 0.5 (0-5) after morphine, respectively (p = 0.41). The median NRS rating under deep inspiration was 3 (0-6) after hydromorphone and 4 (0-7) after morphine, respectively (p = 0.074). The dose ratio of morphine to hydromorphone during PCA was 5.7 (95% confidence interval: 2.9-7.6). Hemodynamics and respiration were stable and did not differ significantly. Postoperative nausea and vomiting were the most frequent adverse events, which were observed in 29% of the patients after hydromorphone and in 35% after morphine, respectively (p = 0.74). Conclusions: There were no significant differences in analgesic efficacy and safety between hydromorphone and morphine when used for postoperative pain therapy with PCA after cardiac surgery with median sternotomy.
CRIS-Team Scopus Importer:2022-08-05
Keywords: adverse events; hydromorphone; morphine; NRS pain rating; Patient-controlled analgesia